A new measure of the degree of controllability for linear system with external disturbance and its application to wind turbines. (February 2018) - Xia, Yaping; Yin, Minghui; Cai, Chenxiao; Zhang, Baoyong; Zou, Yun
This paper is concerned with the measure of degree of controllability (DOC) for linear system with external disturbance. A new measure of DOC, in which the initial condition is regarded as a random vector, is proposed in this paper by solving the fixed-time expected minimum-energy transfer control problem. Since this new measure is dependent on the statistical information of initial condition rather than its estimated value, it is more suitable to apply the proposed measure in the design and optimization of the structural parameters of controlled plants. Furthermore, the simulations on the NREL (National Renewable Energy Laboratory) CART3 wind turbine demonstrate that the relation of the proposed measure to turbine parameters (including rotor inertia and optimum tip speed ratio) coincides with that of the MPPT efficiency to turbine parameters. This indicates that the proposed measure is applicable to guide the design and optimization of the structural parameters of wind turbines. Meanwhile, a mass-spring-damper system is also simulated to validate the proposed measure.